Live discharge from hospice care: psychosocial challenges and opportunities. (8th August 2020) - Wladkowski, Stephanie P.; Wallace, Cara L.
ABSTRACT: Hospice social workers face many challenges in attempts to replicate or supplement the holistic support and unique services hospice provides for individuals discharged alive. This discontinuity in care can impact the types of supports needed by individuals and caregivers, which may or may not be accessible within their community. Patients and families who have access to community-based palliative care programs following a discharge generally tend to navigate the process with fewer challenges. This qualitative study (N = 24) explored both the challenges of the live discharge process and the opportunities within social work practice in the US. Results from this study emphasize the need for a framework to better approach a live discharge to ensure appropriate supports are accessible for all patients and caregivers. Specifically, results highlight both the concrete and psychosocial challenges in live discharges as a result of tension between current eligibility requirements and individual feelings and needs. Social workers also provided suggestions to improve the live discharge process, including attention to communication and preparation. This paper outlines specific challenges of live discharge from hospice, a framework for understanding presented challenges, and implications for policy and practice.